RANCANG BANGUN MODEL DATA UNTUK MANAJEMEN DOKUMEN SISTEM PENJAMINAN MUTU INTERNAL: STUDI KASUS: STMIK KHARISMA MAKASSAR - Mohammad Sofyan S Thayf; Arianti Arianti (SINTECH (Science and Information Technology) Journal, 2021)
To achieve the objectives of the Internal Quality Assurance System, the Quality Standard document must be socialized to each work unit, and the existence of information technology will greatly assist in the distribution and socialization of these documents. This study aims to design and build a data model for storage and management of SPMI documents, especially Standard documents, which are generally in the form of files in print or digital format with a complete structure as a collection of text. With the data model designed, the Standard document is stored in a divided state into a number of entities that represent sub-sections of the document and are structured. This research produces a data model design with a relational system, so that it will produce optimal performance when create, retrieve, update and delete operations are carried out on Standard Documents, and still produce complete information about standard documents, as well as one aspect or context. in Standard documents and their linkages, through application programs and information systems. Testing was carried out by the black-box method of the SPMI document information system prototype which indicated that the data model was successfully implemented and worked well in its application.